2012
DOI: 10.1038/bjc.2012.183
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre randomised phase II trial of gemcitabine alone vs gemcitabine and S-1 combination therapy in advanced pancreatic cancer: GEMSAP study

Abstract: Background:This randomised phase II trial compared gemcitabine alone vs gemcitabine and S-1 combination therapy in advanced pancreatic cancer.Methods:Patients were randomly assigned to 4-week treatment with gemcitabine alone (1000, mg m−2 gemcitabine by 30-min infusion on days 1, 8, and 15) or gemcitabine and S-1 combination therapy (1000, mg m−2 gemcitabine by 30-min infusion on days 1 and 15 and 40 mg m−2 S-1 orally twice daily on days 1–15). The primary end point was progression-free survival (PFS).Results:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
72
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(80 citation statements)
references
References 27 publications
5
72
2
1
Order By: Relevance
“…Ozaka et al reported that the median OS for GEM combined with S-1 was 13.7 months and 8.0 months for GEM alone. Nakai et al (2012) observed that the median OS for GEM combined with S-1 was 13.5 months and 8. 8 months for GEMalone.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Ozaka et al reported that the median OS for GEM combined with S-1 was 13.7 months and 8.0 months for GEM alone. Nakai et al (2012) observed that the median OS for GEM combined with S-1 was 13.5 months and 8. 8 months for GEMalone.…”
Section: Discussionmentioning
confidence: 98%
“…There were no publication biasesdetected by Egger test for the studies in all of our analysis, in the primary endpoint of OS (t=0.74, p=0.474) and PFS (t=0.35, p=0.738) (Higgins et al, 2002;Higgins et al, 2003;Huai et al, 2013). Each article included in the composition of the funnel plot did not find significant bias (Berlin et al, 2002;Scheithauer et al, 2003;Ohkawa et al, 2004;Di Costanzo et al, 2005;Riess et al, 2005;Herrmann et al, 2007;Bernhard et al, 2008;Cunningham et al, 2009;Nakai et al, 2012;Ozaka et al, 2012;Ueno et al, 2013;Sudo et al, 2014).…”
Section: Influent Analysis and Publication Bias Evaluationmentioning
confidence: 93%
“…A phase 2 trial of S-1 for advanced metastatic pancreatic cancer have shown a response rate of 37.5% and the median time to progression and the overall survival time were 3.7 months and 9.2 months [10]. Moreover, multicenter randomized phase 2 trials of a combination of gemcitabine and S-1 (GS) for advanced metastatic pancreatic cancer showed the significant superiority of GS in response rate and progression free survival, but not in overall survival when compared to gemcitabine alone [11,12]. GS as neoadjuvant therapy in patients with resectable or borderline resectable pancreatic cancer may be effective with respect to progression and survival.…”
Section: Introductionmentioning
confidence: 99%
“…Four eligible trials were identified (23)(24)(25)(26). Characteristics of these trials, including chemotherapy regimens and outcome measures, are summarized in Table 1.…”
Section: Characteristics Of Included Trialsmentioning
confidence: 99%
“…Until now, four English published RCTs have been performed to evaluate the survival efficacy between gemcitabine plus S-1 (GS) and gemcitabine monotherapy as first-line chemotherapy in UAPC patients (23)(24)(25)(26). Whether GS could improve treatment efficacy for UAPC was controversial in these four trials.…”
Section: Introductionmentioning
confidence: 99%